Enhancement of Mass and Charge Transfer during Carbon Dioxide Photoreduction by Enhanced Surface Hydrophobicity without a Barrier Layer. Issue 43 (30th June 2022) - Liu, Xuan; Huang, Chengxi; Ouyang, Bo; Du, Yongping; Fu, Boyu; Du, Zhengwei; Ju, Qiang; Ma, Jingjing; Li, Ang; Kan, Erjun
Abstract: The CO2 reduction reaction (CRR) represents a promising route for the clean utilization of renewable resources. But mass‐transfer limitations seriously hinder the forward step. Enhancing the surface hydrophobicity by using polymers has been proved to be one of the most efficient strategies. However, as macromolecular organics, polymers on the surface hinder the transfer of charge carriers from catalysts to reactants. Herein, we describe an in‐situ surface fluorination strategy to enhance the surface hydrophobicity of TiO2 without a barrier layer of organics, thus facilitating the mass transfer of CO2 to catalysts and charge transfer. With less obstruction to charge transfer, a higher CO2, and lower H + surface concentration, the photocatalytic CRR generation rate of methanol (CH3 OH) is greatly enhanced to up to 247.15 μmol g −1 h −1 . Furthermore, we investigated the overall defects; enhancing the surface hydrophobicity of catalysts provides a general and reliable method to improve the competitiveness of CRR. Abstract : The mass transfer of CO2 in aqueous solutions has been enhanced by surface hydrophobic modification. The in‐situ surface fluorination strategy without any organic barrier layer facilitates charge transfer from catalysts to the reactant. With less obstruction to charge transfer, higher CO2 and lower H + surface concentrations, the rate of generation of methanol from the CRR is elevated to up to 247.15 μmol g −1 h −1 .